The Feasibility of Using CT-Guided ROI for Semiquantifying Striatal Dopamine Transporter Availability in a Hybrid SPECT/CT System - Chien-Chin Hsu; Yen-Hsiang Chang; Wei-Che Lin; Shu-Wen Tang; Pei-Wen Wang; Yung-Cheng Huang; Nan-Tsing Chiu (The Scientific World Journal)
A hybrid SPECT/CT system provides accurate coregistration of functional and morphological images. CT-guided region of interest (ROI) for semiquantifying striatal dopamine transporter (DAT) availability may be a feasible method. We therefore assessed the intra- and interobserver reproducibility of manual SPECT and CT-guided ROI methods and compared their semiquantitative data with data from MRI-guided ROIs. We enrolled twenty-eight patients who underwent Tc-99m TRODAT-1 brain SPECT/CT and brain MRI. ROIs of the striatal, caudate, putamen, and occipital cortex were manually delineated on the SPECT, CT, and MRI. ROIs from CT and MRI were transferred to the coregistered SPECT for semiquantification. The striatal, caudate, and putamen nondisplaceable binding potential (BPND) were calculated. Using CT-guided ROIs had higher intra- and interobserver concordance correlation coefficients, closer Bland-Altman biases to zero, and narrower limits of agreement than using manual SPECT ROIs. The correlation coefficients of striatal, caudate, and putamen BPND were good between manual SPECT and MRI-guided ROI methods and even better between CT-guided and MRI-guided ROI methods. Conclusively, CT-guided ROI delineation for semiquantifying striatal DAT availability in a hybrid SPECT/CT system is highly reproducible, and the semiquantitative data correlate well with data from MRI-guided ROIs.